Cession of Life Insurance Policies in securitatem debiti : a Practical Perspective - Sunkel, Kelly (University of Pretoria, 2013)
The security cession of the rights under life policies marries two separate areas of the law: The Law of cession and the Law of Insurance. This makes for a complex union since varying common law and statutory principles find application, and in reality trade practices also play a role. In theory a cession in securitatem debiti may take one of two possible constructions, namely a pledge or a fiduciary security cession, and each has its own advantages and disadvantages. Disparity arose when judicial preference was given to the pledge construction while academics preferred the other. The problem, however, was larger than a disagreement as to the better construction. The underlying problem was that there was a lack regarding clarity as to the practical operation of security cession of life policies, in addition to the problems surrounding the construction thereof. As a solution to this problem some academics have suggested legislative intervention. The South African Law Reform Commission, nevertheless, advised against it in 1991 and was of the opinion that the issue was one which our courts would eventually solve. In the 22 years since then, our courts have merely confirmed its preference for the pledge construction. The intricacies of security cessions of life policies have seen no further judicial development. It is probable that the courts do not have enough practical information at hand to advance this area of the law. An investigation into the operation of such cessions in practice was thus necessary. The outcome of the practical investigation reveals that legislative intervention is indeed a viable solution especially since the issues are too complex for the courts to solve. As part of this work, legislation has been drafted and it is recommended that this is inserted into the Security by Means of Movable Property Act .
Keywords: Life Insurance; Security Cession